Is there a relation between Tefal’s communication strategy and the consumer’s decision making process? : - Haász, Alexia (2025)
This thesis examines the relations between consumers decision making and Tefal brand's communication strategy. Consumers decision making depends on many different aspects: their knowledge, preferences, demographical background as well as their education and economical status. Tefal positions itself as a premium brand, and leverages it in its communication strategy. This thesis is examining if Tefal brand efficitently communicates about sustainability, price and quality, as well as how their communication strategy influences customers decision making process.